Laminin and Integrin in LAMA2-Related Congenital Muscular Dystrophy: From Disease to Therapeutics - Barraza-Flores, Pamela; Bates, Christina R.; Oliveira-Santos, Ariany; Burkin, Dean J. (Frontiers in Molecular Neuroscience, 2020)
Laminin-α2 related Congenital Muscular Dystrophy (LAMA2-CMD) is a devastating neuromuscular disease caused by mutations in the LAMA2 gene. These mutations result in the complete absence or truncated expression of the laminin-α2 chain. The α2-chain is a detrimental component of the laminin-211 and laminin-221 isoforms, predominant in healthy adult skeletal muscle. Mutations in this chain result in progressive skeletal muscle degeneration as early as neonatally. Laminin-211/221 are ligands for muscle cell receptors integrin-α7β1 and α-dystroglycan. LAMA2 mutations are correlated with integrin-α7β1 disruption in skeletal muscle. In this review, we will summarize laminin-211/221 interactions with integrin-α7β1 in LAMA2-CMD muscle. Additionally, we will summarize recent developments using upregulation of laminin-111 in the sarcolemma of laminin-α2 deficient muscle. We will discuss potential mechanisms of action by which laminin-111 is able to prevent myopathy. These published studies demonstrate that laminin-111 is a disease modifier of LAMA2-CMD through different methods of delivery. Together these studies show the potential for laminin-111 therapy as a novel paradigm for the treatment of LAMA2-CMD.